Variational Image Denoising Approach with Diffusion Porous Media Flow - Tudor Barbu (Abstract and Applied Analysis)
A novel PDE-based image denoising approach is proposed in this paper. One designs here a nonlinear filter for image noise reduction based on the diffusion flow generated by the porous media equation ∂u/∂t=Δβ(u), where β is a nonlinear continuous function of the form β(u)=λum, 0<m<1. With respect to standard 2D Gaussian smoothing and some nonlinear PDE-based filters, this one is more efficient to remove noise from degraded images and also to reduce “staircasing” effects and preserve the image edges.